PERTUMBUHAN SEMAI R. mucronata PADA TAMBAK WANAMINA DENGAN LEBAR SALURAN INLET DAN KOMPOSISI MANGROVE YANG BERBEDA - Ruli Nur Hidayanti; Rini Budi Hastuti; Endah Dwi Hastuti (Departemen Biologi, Fakultas Sains dan Matematika Undip, 2016)
Fishpond as aqua culture in certain regions are managed intensively to obtain optimum results. Rising the areas of fishpond induced decrease of mangroves areas due to land conversion. Managing sytem of fishpond in association with mangrove forests began to be developed and known as silvofishery. R. mucronata is one type of mangrove which has an important role for the environment of fishpond. This research aims to know the growth of R. mucronata in duct inlet of silvofishery with different width and mangrove compositions. This research was carried out axperimentally using Random Design Group (RAK) factorial pattern 2x3. The first factor is the compositions of mangrove (single & mix) and the second factor is inlet width (1 m. 2m, and 3 m). The result of the ANOVA analysis showed that height, diameter growth on each inlet width and composition of different mangrove showed that there is no significant difference of growth during two months research. However on L3K1 (3 meters inlet width with a single mangrove composition) produce heigh and diameter growth were better than on the other inlet width and mixture composition of mangrove. Key words : Growth, Seedling, R. mucronata, Silvofishery.